The interaction of BH2NH2 with HNZ (Z: O, S) in the gas phase: Theoretical study of the blue shift of N-H...H-B dihydrogen bonds and the red shift of N-H...O and N-H...S hydrogen bonds - Trung, Nguyen Tien; Hue, Tran Thanh (Vietnam Journal of Chemistry, 2014)
Theoretical calculations at the MP2/6-311++G(2d,2p) level were performed to study the origin of the B-H...H-N blue-shifting dihydrogen bonds in the complexes of BH2NH2...HNZ          (Z = O, S). The stably optimized cyclic structures of the complexes are displayed in figure 1, with interaction energies as table 1. The blue shift of the N5-H7 bond stretching frequencies is observed in the B9-H4...H7-N5 dihydrogen bonds for BH2NH2...HNO and BH2NH2...HNS, corresponding to contraction of the N5-H7 bonds (except for slight elongation of the N5-H7 bond found in the complex BH2NH2...HNS), increase of stretching frequencies and decrease of infrared intensities respectively.